Reduction of oxidative damage caused by drought stress in Camelina (Camelina sativa L.) seedlings using silicone - Nasrin Teimoori; Mokhtar Ghobadi; Danial Kahrizi (علوم و فناوری بذر ایران)
Drought is one of the most important stresses in reducing plant growth, especially in the seed germination stage. Oxidative stress is one of the consequences of drought in plants. To investigate the reduction of oxidative stress damage caused by drought stress by using silicon in the initial stages of camellia seedling growth, a factorial experiment as completely randomized design was carried out in the seed laboratory of Razi University with three replications. The factors include two camelina genotypes, four levels of drought stress (0, -3, -6, -9 bar using PEG-6000) and five levels of silicon (0, 2, 4, 6 and 8 mM). According to the results, drought stress increased the activity of antioxidant enzymes including peroxidase, catalase and superoxide dismutase and the amount of malondialdehyde, but it decreased the growth characteristics of seedlings and the amount of soluble proteins. The consumption of silicon (especially by 6 and 8 mM concentrations) increased the activity of antioxidant enzymes and seedling growth characteristics. So, consumption of 8 mM silicon increased peroxidase activity by 23.2%, catalase activity by 13.4%, superoxide dismutase activity by 41%, malondialdehyde by 19.1% and protein content. Soluble was 10.8%. Therefore, the consumption of silicon 8mM by activating the antioxidant system moderated the effects of oxidative stress caused by drought stress and increased the growth characteristics of camellia seedlings.